BUSINESS FEASIBILITY ANALYSIS OF UPJA CAHAYA BINTANG (AGRICULTURAL MACHINERY SERVICE UNIT) IN MUARA ENIM, SOUTH SUMATERA - Rabecha Maros Framita; Piranti Herdaning Putri; Fitri Yunda Sari; Dwi Oktarina Aryani; Agusri Agusri; Intan Avrilikasari (Syarif Hidayatullah State Islamic University Jakarta, 2025)
The Agricultural Equipment and Machinery Service (AEMS) Business or Usaha Pelayanan Jasa Alat dan Mesin Pertanian (UPJA) plays a crucial role in improving farming efficiency through mechanization, especially for farmers without access to agricultural machinery. This study analyzes the feasibility of Cahaya Bintang in Muara Enim Regency from financial, technical, and economic perspectives through a descriptive quantitative approach. The results indicate that with total operational costs of IDR 741,933,333 and total revenue of IDR 768,000,000, the business generates a profit of IDR 26,066,666 and an R/C Ratio of 1.04, which indicates financial feasibility. However, the low profit margin highlights the need for operational efficiency improvements, such as optimizing machinery utilization, reducing fuel costs, and diversifying services. Other recommended strategies include strengthening cooperation with farmer groups, enhancing machinery maintenance, and institutional support to improve competitiveness and business sustainability.